Development Outcomes of Old and New Sources of International Development Finance in Sri Lanka. Issue 4 (December 2017) - Sarvananthan, Muttukrishna
This research article compares and contrasts development outcomes of 'traditional' or 'old' and 'emerging' or 'new' sources of international development finance in Sri Lanka during the ceasefire time (2002–2005) when it depended on former sources and the post-civil war period (2009–2012) when it depended heavily on the latter sources. It also compares and contrasts the development outcomes in Sri Lanka (a lower middle income country), which depended heavily on the 'emerging' or 'new' sources of international development finance, and Nepal (a low income country), which depended on 'traditional' or 'old' sources of international development finance, during the first five years after the end of their respective civil wars. Although the causality is difficult to establish, the data presented herein demonstrates that while GDP growth and per capita income growth have been greater under the new international development finance regime in Sri Lanka, positive changes in the rates of inflation, unemployment, and poverty have been greater under the old international development finance regimes in Sri Lanka and Nepal.